2011
DOI: 10.1109/tgrs.2010.2057513
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Remote Sensing and Hydrologic Modeling for Flood Inundation Mapping in Lake Victoria Basin: Implications for Hydrologic Prediction in Ungauged Basins

Abstract: Floods are among the most catastrophic natural disasters around the globe impacting human lives and infrastructure. Implementation of a flood prediction system can potentially help mitigate flood-induced hazards. Such a system typically requires implementation and calibration of a hydrologic model using in situ observations (i.e., rain and stream gauges). Recently, satellite remote sensing data have emerged as a viable alternative or supplement to in situ observations due to their availability over vast ungaug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
123
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(150 citation statements)
references
References 38 publications
7
123
0
9
Order By: Relevance
“…The analysis showed the value of integrating satellite data such as precipitation, land cover type, topography, and other products with space-based flood inundation extents as inputs to the distributed hydrologic model. The results confirmed that the quantification of flooding extent through remote sensors can help to calibrate and evaluate hydrologic models and, therefore, improve hydrologic prediction and flood management strategies, especially in poorly gauged catchments (Khan et al, 2011).…”
Section: Assessing Vulnerability To Floodingsupporting
confidence: 67%
See 1 more Smart Citation
“…The analysis showed the value of integrating satellite data such as precipitation, land cover type, topography, and other products with space-based flood inundation extents as inputs to the distributed hydrologic model. The results confirmed that the quantification of flooding extent through remote sensors can help to calibrate and evaluate hydrologic models and, therefore, improve hydrologic prediction and flood management strategies, especially in poorly gauged catchments (Khan et al, 2011).…”
Section: Assessing Vulnerability To Floodingsupporting
confidence: 67%
“…For example, Khan et al (2011) implemented a raster-based distributed hydrologic model, coupled routing and excess storage (CREST) for the Nzoia basin, a subbasin of Lake Victoria in Africa. Terra satellitebased MODIS data and advanced spaceborne thermal emission and reflection radiometer (ASTER) data were used to produce flood inundation maps over the region.…”
Section: Assessing Vulnerability To Floodingmentioning
confidence: 99%
“…However, the ability to calibrate a model using satellite data, even in combination with traditional in situ data, is still a challenging topic. Scientific work in this field goes in many directions: Rhoads et al (2001) used satellite-derived LST to validate a land-surface model, Caparrini et al (2004) and Sini et al (2008) assimilated remotely sensed measurements into a land-surface model to estimate the surface turbulent fluxes, Brocca et al (2011a) analyzed different remotely sensed soil humidity estimations with the perspective of using them in hydrological modeling, White and Lewis (2011) used satellite imagery to monitor the dynamics of wetlands of the Australian Great Artesian basin and Khan et al (2011) have recently proposed a procedure to calibrate a fully distributed hydrological model using satellite-derived flood maps.…”
Section: Introductionmentioning
confidence: 99%
“…*Floods are among the most destructive natural hazards that affect humans, property and settlements (Khan et al, 2011;Dano Umar et al, 2011, Dano Umar et al, 2014Ayobami and Rabi'u 2012). Flooding is a devastating natural phenomenon that affects and disrupts the wellbeing of the societies especially poor people who are vulnerable to disaster due to limitation of their resources.…”
Section: Introductionmentioning
confidence: 99%